NUTRITIONAL STATUS ASSESSMENT OF ORPHANAGE CHILDREN IN RAWALPINDI - Mehwish Riaz; Naila Azam; Humaira Mahmood; Raima Asif; Nazish Khan; Fatima Ali Raza Mughal (Pakistan Armed Forces Medical Journal, 2021)
Objective: To evaluate the health and nutritional status of the orphanage, to find frequency of nutritional deficiencies by physical examination findings and to assess their dietary intake and contrast it with individual recommended daily allowances.